Catheter ablation for atrial fibrillation in patients with persistent left superior vena cava: Case series and systematic review - Gao, Mingyang; Bian, Yang; Huang, Lihong; Zhang, Jingrui; Li, Changyi; Liu, Nian; Liu, Xiaoxia; Zuo, Song; Guo, Xueyuan; Wang, Wei; Zhao, Xin; Long, Deyong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Persistent left superior vena cava (PLSVC) is the most common form of thoracic venous abnormality. Catheter ablation (CA) for atrial fibrillation (AF) can be complicated by the existence of PLSVC, which could act as an important arrhythmogenic mechanism in AF. Methods and Results We reported a case series of patients with PLSVC who underwent CA for AF at our center between 2018 and 2021. A systematic search was also performed on PubMed, EMBASE, and Web of Science for research reporting CA for AF in patients with PLSVC. Sixteen patients with PLSVC were identified at our center. Ablation targeting PLSVC was performed in 5 patients in the index procedures and in 4 patients receiving redo procedures. One patient experienced acute procedure failure. After a median follow-up period of 15 months, only 6 (37.5%) patients remained free from AF/atrial tachycardia (AT) after a single procedure. In the systematic review, 11 studies with 167 patients were identified. Based on the included studies, the estimated prevalence of PLSVC in patients undergoing CA for AF was 0.7%. Ablation targeting PLSVC was performed in 121 (74.7%) patients. Major complications in patients with PLSVC receiving AF ablation procedure included 4 cases of cardiac tamponades (2%), 3 cases of cardiac effusion (1.5%), 1 case of ischemic stroke, and 3 cases of phrenic nerve injury (1.5%) (1 left phrenic nerve and 2 right phrenic nerve). Pooled analysis revealed that after a median follow-up period of 15.6 months (IQR 12.0-74.0 months), the long-term AF/AT-free rate was 70.6% (95% CI 62.8%-78.4%, I2=0.0%) (Central illustration). Different ablation strategies for PLSVC were summarized and discussed in the systematic review. Conclusion In patients with PLSVC, recurrence of atrial arrhythmia after CA for AF is relatively common. Ablation aiming for PLSVC isolation is necessitated in most patients. The overall risk of procedural complications was within an acceptable range.